The Effectiveness of Local Wisdom-Based Integrative Thematic English Education Games in 2013 Curriculum - Indah - Arvianti; Ana - Wahyuni (Master Program in Linguistics, Diponegoro University, 2020)
The 2013 curriculum at the elementary level emphasizes the competence of students focused on character education. However, this curriculum does not include English as a means of mastering global knowledge. Based on this, the purposes of this research are to fulfill the absence of English subject which has not been integrated thematically in 2013 curriculum and to examine the effectiveness of English learning model using local wisdom-based thematic integrative education games for the 1st grade of elementary school students as well as to maintain local wisdom as a strategy to construct the character of youth nation. Data collection methods are interview, observation, questionnaire, and literature study. The other method is the pre-test and post-test experimental design. Respondents of this study are 148 students of the 1st grade elementary school in 17 elementary schools in Central Semarang. The results of both tests show that this model has proven to be effective in increasing the English competence of those students. This learning media is considered appropriate because this media is very interesting and fun so that it can encourage students to learn English and make students enthusiastic in learning so that it gives good results.